Assessment of Wheat and Quality Protein Maize Quality - Avsthi, Rajat; Rawat, Kushanak (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
A study was conducted to prepare protein enriched biscuits which could be used as a protein supplemented snack food. The study evaluated the effect of substituting soy-flour 20%, 15% and 10% in biscuit production. Biscuits were enriched with soy-flour T0 (control with no soy flour), T1 (20 %), T2 (15 %) and T3 (10 %). Sensory, nutrient estimation and Microbial qualities of biscuits were evaluated. Organoleptic test of biscuits showed that with regard to flavour and taste, body and texture, colour and appearance and overall acceptability, sensory characteristics of T3 were found to be the best. The other treatments T0, T1 and T2 were also found acceptable. In nutrient estimation of biscuits, moisture content was found maximum in treatment T1, protein content was maximum in treatment T1, fat content was highest in treatment T1, ash content was highest in treatment T1, carbohydrate was found maximum in treatment T3, calorie content was maximum in T1, iron content was maximum in T2 and calcium content was maximum in treatment T1. Best treatment was T1 among T0, T1, T2 and T3. The soy flour added product-biscuit has good shelf life. The product is ready -to-eat so don't require much time for preparation. It is a compact source of energy and nutrients including protein, fat, Iron, calcium etc. It can be concluded that Sensory scores indicated high acceptability for treated biscuit samples. Protein and fat contents of biscuits increased with increasing soy fortifications. Substitution with soy-flour did not adversely affect qualities.